Mental well-being, work engagement, and work-related and personal resources among nurse managers: A structural equation model - Marja Hult; Anja Terkamo-Moisio (Elsevier, 2023)
Background: Nurse managers are central to guaranteeing quality healthcare outcomes. However, their position is very demanding and special attention should be paid to their mental well-being. Good mental well-being at work is associated with overall occupational well-being, increasing nurse managers' intention to stay in the profession and their commitment to their organization. However, little is known about nurse managers' personal and work-related resources that support good mental well-being. Objective: To explore work-related and personal resources associated with nurse managers' work engagement and mental well-being. Design: A cross-sectional survey study. Participants: Finnish nurse managers (n = 366) including ward managers (n = 332), chief nurses (n = 24), and administrative head nurses (n = 6). Methods: Nationwide online survey data was collected with a self-administered questionnaire in February 2023 from the members of one health and social care workers' trade union. The relationships between nurse managers' personal (psychological capital and calling) and work-related (job resources and social support) resources, work engagement and mental well-being were analysed using structural equation modeling. Nurse managers were also divided into two groups based on their mental well-being score: those with and without depression. The study is reported following the guidelines for Strengthening the Reporting of Observational Studies in Epidemiology (STROBE). Results: Nurse managers who had depression (27%) were associated with less personal and work-related resources compared to managers without depression. Work engagement correlated strongly with mental well-being. A structural equation model that indicated positive significant total effects of work engagement (β = 0.38), social support (β = 0.26), job resources (β = 0.19), and psychological capital β = 0.28) and calling (β = 0.13) with mental well-being had an excellent fit. Conclusion: Nurse managers' mental well-being can be supported by organisational strategies and national policies that enhance leadership skills and increase work-related resources, which, in turn, can manifest as psychological and professional capital and a sense of meaningfulness in work.Globally, the healthcare sector needs resilient and healthy nurse managers to respond to current and future challenges. They are key players in safeguarding the well-being and commitment of nursing staff and thereby improving the quality of care.